Hearing microwaves the microwave auditory phenomenon. - Lin, James C. (IEEE Antennas & propagation magazine.)
The microwave auditory phenomenon, or the microwave hearing effect, pertains to the hearing of short pulses of modulated microwave radiation at high peak power by humans and laboratory animals. Anecdotal and journalistic reports of the hearing of microwave pulses persisted throughout the 1940s; and 1950s. The first scientific report of the phenomenon appeared in 1961. The effect has been observed for RF exposures across a wide range of frequencies (450-3000 MHz). It can arise, for example, at an incident energy-density threshold of 400 mJ/m2 for a single 10-microsecond-wide pulse of 2450 MHz microwave energy, incident on the head of a human subject. And it has been shown to occur at an SAR threshold of 1.6 kW/kg for a single 10-microsecond-wide pulse of 2450 MHz microwave energy, impinging on the head. A single microwave pulse can be perceived as an acoustic click or knocking sound, and a train of microwave pulses to the head can be sensed as an audible tune, with a pitch corresponding to the pulse-repetition rate (a buzz or chirp). Note that the SAR threshold of 1.6 kW/kg is about 1000 times higher than that allowable by FCC rules for cellular mobile telephones.